Iron maltol crystal form DCIII as well as preparation method and application thereof

By recrystallizing and drying in organic solvents, the new crystal form DCIII of maltol iron was developed, solving the problems of low solubility and complex preparation of existing crystal form II, achieving higher bioavailability and better stability.

CN119591573APending Publication Date: 2025-03-11BIRDO (SHANGHAI) PHARM R&D CO LTD

Patent Information

Application Number
CN202411386220.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The existing crystal form II of maltol iron has low solubility, resulting in poor drug efficacy and low bioavailability. At the same time, the preparation method is complicated, the crystal form control is difficult, and mixed crystals are prone to occur.

Method used

A new ferrous maltol crystal form DCIII was developed to obtain crystal form DCIII with improved solubility and stability by recrystallization and drying in an organic solvent.

Benefits of technology

The solubility of crystalline DCIII in simulated gastric juice, intestinal fluid and water is significantly improved, and the bioavailability is enhanced. The preparation method is simple and the crystalline form is easy to control, which avoids the risk of mixed crystals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591573A_ABST
    Figure CN119591573A_ABST
Patent Text Reader

Abstract

The invention relates to a crystal form of a compound I, a preparation method of the crystal form, and application of the crystal form in preparation of iron deficiency related treatment medicines for treating anemia accompanied with or not accompanied with iron deficiency. The novel crystal form of the compound I provided by the invention has the advantages of high solubility, good chemical stability, solid stability, mechanical stability and humidity stability, simple preparation method, easiness in crystal form control, low production amplification cost and the like, and has important value for development of the medicine in the future. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of drug crystal forms, and in particular to a maltol iron crystal form DCIII and a preparation method and application thereof. Background Art

[0002] Ferrous maltol is a new oral trivalent iron compound developed by Shield Therapeutics in the UK. It was approved by the European Medicines Agency in 2016 to treat iron deficiency symptoms in adults. On July 25, 2019, the drug was officially approved by the US Food and Drug Administration to have the same effect.

[0003] Maltol iron is an iron ion complex. Unlike iron salt compounds, it dissociates when taken into the gastrointestinal tract, and the iron ions and maltol are absorbed separately. The iron ions are taken up by the intestinal wall cells and transferred to transferrin and ferritin, thereby increasing the concentration of iron ions in the serum, including the saturation of ferritin and transferrin, to achieve the effect of iron supplementation.

[0004] In clinical applications, maltol ferric is a drug for the treatment of iron deficiency in adults with a low incidence of adverse reactions, high bioavailability, and low iron overload, and is well tolerated. It is a reliable drug to replace intravenous iron therapy, and is also an ideal alternative for patients who are intolerant to existing oral iron preparations and have poor treatment effects.

[0005] Maltol iron is a complex containing a trivalent iron cation and three maltol anions, with a molecular formula of (C6H5O3)3Fe and the structural formula is as follows:

[0006]

[0007] Ferrous maltol is a drug for treating iron deficiency in adults with low incidence of adverse reactions, high bioavailability, low iron overload, and good tolerance. However, in the various crystal forms of ferrous maltol reported in existing literature, there is a common problem of low solubility, resulting in poor efficacy and low bioavailability.

[0008] Ferric maltol is a polymorphic compound. The phenomenon of drug polymorphism refers to the phenomenon that solid drug molecules have two or more different crystal forms. Because different crystal forms have different physical and chemical properties, different crystal forms of solid drug molecules may have different dissolution and absorption in the body, which in turn affects the clinical efficacy and safety of the drug to a certain extent. Especially for poorly soluble solid drugs, the effect of the crystal form on bioavailability will be greater. Therefore, drug crystal form is an important part of the research and development process of solid drugs, and is also an important part of drug quality control.

[0009] CN107001310B discloses four polymorphs of maltol iron, namely anhydrous crystal forms I, II, IV, and solvate crystal form III. Among them, crystal form I has poor stability and is easily converted into crystal form II; crystal form IV is difficult to prepare, and solvate crystal form III contains organic solvents and has large toxic side effects, so it cannot be used as a medicinal crystal form. At the same time, in paragraphs

[0139] and

[0221] to

[0225] of CN107001310B, research data of crystal form I, crystal form II, crystal form III and crystal form IV are disclosed, and it is concluded that crystal form II is the main form, from which it can be seen that crystal form II is the most important and thermodynamically stable and most advantageous crystal form.

[0010] Form II is the most important and most advantageous form. Although it is a stable form, it has low solubility, poor efficacy and low bioavailability. At the same time, in paragraphs

[0197] and

[0198] of patent CN107001310B, it is disclosed that even if crystal seeds of Form II are added, Form I is still obtained at 2 hours and 20 hours. This shows that in the preparation method of Form II in the prior art, Form I is easy to appear, which easily leads to the final product being a mixed crystal, which brings great challenges to the crystal form control of the product.

[0011] In summary, the art is in urgent need of a new crystal form of maltol iron with good solubility and stability, and the obtained new crystal form preferably has a simple preparation method, easy crystal form control, and no mixed crystal. On the one hand, the risk of crystal transformation can be avoided, and on the other hand, it is easy for the drug to be absorbed and the bioavailability is improved. At the same time, it also has good production scalability to meet the bioavailability of the drug, suitable for industrial development, and all aspects of comprehensive performance meet the requirements of new crystal forms for medicinal development.

[0012] The inventors of the present application unexpectedly discovered that different crystalline forms of Compound I provided by the present invention have advantages in physicochemical properties, formulation processing performance and bioavailability, such as advantages in at least one of the aspects of melting point, solubility, hygroscopicity, purification effect, stability, adhesion, compressibility, fluidity, in vitro and in vivo dissolution, and bioavailability, which provides a better choice for the development of drugs containing Compound I and is of great significance. Summary of the invention

[0013] In view of the above-mentioned defects of the prior art, the present invention provides a ferric maltol crystal form DCIII, which has improved solubility and good stability, and the preparation method is simple and the crystal form is easy to control. To this end, the present invention also provides a preparation method of the ferric maltol crystal form DCIII. In addition, the present invention also provides the use of the ferric maltol crystal form DCIII.

[0014] According to the purpose of the present invention, the present invention provides a crystalline form of Compound I.

[0015] Furthermore, the crystalline form of Compound I provided by the present invention may be crystalline form DCIII (hereinafter referred to as crystalline form DCIII).

[0016] On the one hand, using Cu-Ka radiation, the X-ray powder diffraction of the crystalline form DCIII has characteristic peaks at one, two, or three of the diffraction angles 2theta values ​​of 13.8°±0.2°, 9.4°±0.2°, and 14.4°±0.2°.

[0017] Further, using Cu-Ka radiation, the X-ray powder diffraction of the crystalline form DCIII has characteristic peaks at one, two, or three of the diffraction angles 2theta of 6.8°±0.2°, 10.6°±0.2°, and 15.1°±0.2°; preferably, the X-ray powder diffraction of the crystalline form DCIII has characteristic peaks at three of the diffraction angles 2theta of 6.8°±0.2°, 10.6°±0.2°, and 15.1°±0.2°.

[0018] Further, using Cu-Ka radiation, the X-ray powder diffraction of the crystalline form DCIII has characteristic peaks at one, two, or three of the diffraction angles 2theta of 15.8°±0.2°, 22.9°±0.2°, and 24.0°±0.2°; preferably, the X-ray powder diffraction of the crystalline form DCIII has characteristic peaks at three of the diffraction angles 2theta of 15.8°±0.2°, 22.9°±0.2°, and 24.0°±0.2°.

[0019] On the other hand, using Cu-Ka radiation, the X-ray powder diffraction of the crystalline form DCIII has characteristic peaks at diffraction angles 2theta of 6.8°±0.2°, 9.4°±0.2°, 10.6°±0.2°, 12.1°±0.2°, 13.0°±0.2°, 13.8°±0.2°, 14.4°±0.2°, 15.1°±0.2°, 15.8°±0.2°, 22.9°±0.2°, 24.0°±0.2°, or at one, or two, or three, or four, or five, or six, or seven, or eight, or nine, or ten, or 11.

[0020] Without limitation, the X-ray powder diffraction pattern of the crystalline DCIII is substantially as follows Figure 1 shown.

[0021] In a non-limiting manner, the crystal form DCIII begins to have an endothermic peak at around 292 degrees, and the differential scanning calorimetry analysis diagram is basically as follows: Figure 2 shown.

[0022] Without limitation, the crystalline form DCIII is an anhydrous crystalline form.

[0023] According to the purpose of the present invention, the present invention also provides a method for preparing the crystalline form DCIII, the preparation method comprising:

[0024] A certain amount of compound I is weighed and added into a glass bottle, a certain amount of organic solvent or a mixed solvent of organic solvents is added, and the mixture is fully shaken, recrystallized at a certain temperature, and the solid is separated by centrifugation and dried at a certain temperature to obtain the crystalline form DCIII.

[0025] Specifically, a method for preparing ferric maltol crystal form DCIII comprises placing ferric maltol in an organic solvent, recrystallizing at a temperature of -20°C to 30°C, and obtaining ferric maltol crystal form DCIII after centrifugation and drying.

[0026] Further, the selected organic solvent is preferably chloroform;

[0027] Furthermore, the selected recrystallization temperature is preferably -20 to 30 degrees, more preferably 0 to 5 degrees;

[0028] Furthermore, the selected drying temperature is preferably 100 to 180 degrees, more preferably 150 degrees;

[0029] According to the purpose of the present invention, the present invention also provides a pharmaceutical composition, which comprises an effective therapeutic amount of crystalline DCIII and a pharmaceutically acceptable carrier or excipient;

[0030] Furthermore, the present invention provides use of crystalline DCIII in the preparation of a medicament for preventing or treating iron deficiency with or without anemia in a subject.

[0031] The crystal form DCIII provided by the present invention has the following beneficial effects:

[0032] 1) Compared with the prior art, the crystalline form DCIII of the present invention has higher solubility.

[0033] Compared with the prior art, the crystal form DCIII of the present invention has higher solubility in SGF (simulated gastric fluid), FaSSIF (simulated intestinal fluid in the fasting state), FeSSIF (simulated intestinal fluid in the fed state) and water. At 1 hour and 2 hours, the solubility of the crystal form DCIII of the present invention is 2 times that of Form II reported in the prior art CN107001310B. Higher solubility is conducive to improving the absorption of drugs in the human body, improving the bioavailability of drugs, and achieving better therapeutic effects with less drug loading; in addition, under the premise of ensuring the efficacy of drugs, reducing the drug loading can reduce the toxic and side effects of drugs and improve the safety of drug use, which has important clinical significance.

[0034] 2) Compared with the prior art, the process for preparing the crystal form DCIII of the present invention is simpler and the crystal form control is easier.

[0035] According to the above analysis of the prior art, Form II is the most important and most advantageous form. However, the

[0197] field of patent CN107001310B discloses that Form I is obtained without adding Form II seed crystals. Moreover, the

[0198] field of patent CN107001310B also discloses that even if Form II seed crystals are added, Form I is still obtained at 2 hours and 20 hours. This shows that in the preparation method of Form II in the prior art, Form I is easy to appear, which easily leads to the result that the final product is a mixed crystal, which brings great challenges to the crystal form control of the product. The preparation process of Form DCIII of the present invention is simple, and the crystal form control is easier. In the case of not adding seed crystals, the obtained solid is still pure Form DCIII, and no mixed crystals will appear, which provides convenience for subsequent industrial development.

[0036] 3) The crystalline DCIII provided by the present invention has good stability.

[0037] The crystal form DCIII of the present invention is placed under the conditions of 25°C / 60%RH (relative humidity), 40°C / 75%RH, and 60°C / 75%RH for 2 weeks, respectively, and the crystal form remains unchanged, indicating that the crystal form DCIII has good physical stability, especially under the accelerated condition of 40°C / 75%RH and the high temperature and humidity condition of 60°C / 75%RH, the crystal form remains stable after being placed for 2 weeks without crystal transformation, which further illustrates that the crystal form DCIII still has good physical stability even under the conditions of high temperature and high humidity, which ensures that the drug is not prone to crystal transformation during subsequent processes, production and transportation; in addition, the chemical purity of the crystal form DCIII does not change before and after being placed under the conditions of 25°C / 60%RH (relative humidity), and the purity is maintained at more than 99%, indicating that the crystal form DCIII has good chemical stability. In addition, even under the accelerated condition of 40°C / 75%RH and the high temperature and humidity condition of 60°C / 75%RH, the chemical purity still does not decrease significantly, which further illustrates that the crystal form DCIII has good chemical stability. Good physical and chemical stability ensures that the drug can maintain stable quality and ensure drug quality and efficacy during subsequent formulation development and process production, as well as drug production and transportation, which is of great significance.

[0038] In addition, the crystal form DCIII has good mechanical stability. Crystal form DCIII did not undergo crystal transformation before and after grinding, and no significant decrease in the crystallinity of the sample was observed, which shows that the crystal form DCIII has good mechanical stability. Good mechanical stability can ensure that the sample will not easily undergo crystal transformation due to external forces such as mechanical grinding and crushing during the later formulation process, reducing the risk of crystal transformation during the formulation process and improving the developability of the formulation process.

[0039] Furthermore, the crystal form DCIII has good humidity stability. After the solid samples of the crystal form DCIII were placed open at ~30% degrees / 22.5% RH, ~30% degrees / 45% RH, and ~30% degrees / 80% RH for 2 weeks, the crystal form was still DCIII and did not change, which shows that the crystal form DCIII has good stability under low humidity and high humidity conditions. During the preparation, storage and preparation production of raw materials, the ambient humidity will vary with factors such as season, location, and weather. Therefore, the stability of the sample under different humidity is a relatively important parameter for investigation. The crystal form DCIII of the present invention has good stability under low humidity and high humidity conditions, which will bring convenience to the sample production, storage, and preparation processes, reduce the risk of crystal transformation, and improve product stability.

[0040] Crystal stability is of great significance to drug development. If crystal transformation occurs, it will directly affect the solubility of the drug and then affect the bioavailability of the drug, thereby changing the efficacy of the drug. Good chemical stability can ensure that the drug produces almost no new impurities or the impurity content hardly increases during storage, thereby ensuring the safety of the drug. Good mechanical stability can also improve the drug's tolerance to mechanical damage during the formulation process and reduce the risk of crystal transformation. Good humidity stability can ensure that the sample will not easily undergo crystal transformation due to changes in environmental humidity during later storage, transportation, and formulation process preparation, reducing the risk of crystal transformation during sample storage, transportation, and formulation process, and improving the product's developability.

[0041] Therefore, the good physicochemical stability, good mechanical stability and good humidity stability of crystalline DCIII provide guarantees for the subsequent production and development of drugs and have high industrial development value.

[0042] Furthermore, the crystalline form DCIII of the present invention also has the following beneficial effects:

[0043] 1) The crystal form DCIII of the present invention has low hygroscopicity.

[0044] According to the Pharmacopoeia (Chinese Pharmacopoeia 2020 Edition General Principles 9103 Drug Hygroscopicity Experimental Guidelines, Experimental Conditions: 25±1°C, 80% Relative Humidity) method, the hygroscopicity of the crystalline DCIII of the present invention was investigated, and the results showed that the crystalline DCIII gained 1.03% weight due to moisture. In addition, regarding the description of hygroscopic characteristics and the definition of hygroscopic weight gain (Chinese Pharmacopoeia 2020 Edition General Principles 9103 Drug Hygroscopicity Experimental Guidelines, Experimental Conditions: 25±1°C, 80% Relative Humidity), the weight gain category of the crystalline DCIII is: the weight gain due to moisture is less than 2.0% but not less than 0.2%, which is slightly hygroscopic. This result shows that the crystalline DCIII has low hygroscopicity. Low hygroscopicity can ensure that the sample can maintain a low moisture weight gain without deliquescence during later production, processing, storage and transportation, thereby ensuring the stability of the drug quality.

[0045] The concept, specific structure and technical effects of the present invention will be further described below in conjunction with the accompanying drawings to fully understand the purpose, characteristics and effects of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 This is the XPRD spectrum of the ferric maltol crystal form DCIII prepared in Example 1 of the present invention;

[0047] Figure 2 is the DSC spectrum of the ferric maltol crystal form DCIII prepared in Example 1 of the present invention;

[0048] Figure 3 This is the XPRD spectrum of the ferric maltol crystal form DCIII prepared in Example 2 of the present invention;

[0049] Figure 4 This is the XPRD spectrum of the stability of the maltol iron crystal DCIII prepared in Example 1 of the present invention before and after being placed;

[0050] Figure 5 This is the XPRD spectrum of the maltol iron crystal DCIII prepared in Example 1 of the present invention before and after grinding;

[0051] Figure 6 This is the XPRD spectrum of the maltol iron crystal DCIII prepared in Example 1 of the present invention after being placed at different humidity levels; DETAILED DESCRIPTION

[0052] In order to make the technical means, creative features, objectives and effects of the invention easier to understand, the invention is further described below with reference to specific illustrations. However, the invention is not limited to the following implementation cases.

[0053] It should be noted that the structures, proportions, sizes, etc. illustrated in the drawings of this specification are only used to match the contents disclosed in the specification so as to facilitate understanding and reading by persons familiar with this technology. They are not used to limit the conditions under which the present invention can be implemented, and therefore have no substantive technical significance. Any structural modification, change in proportion or adjustment of size, without affecting the effects and purposes that can be achieved by the present invention, should still fall within the scope of the technical contents disclosed by the present invention.

[0054] XRPD, namely X-ray powder diffraction, the X-ray powder diffraction pattern of the present application was collected on a Bruker D2PHASER X-ray powder diffractometer. The method parameters of X-ray powder diffraction are as follows: X-ray source: Cu Ka; Ka1 (A): 1.54060; Ka2 (A) 1.54439; Ka2 / Ka1 intensity ratio: 0.50; voltage: 30 kilovolts (kV); current: 10 milliamperes (mA); scanning range: 3.0-40.0°.

[0055] DSC, namely differential scanning calorimetry, the differential scanning calorimetry (DSC) graph of the present application was collected on TA company DSC X3, and the method parameters of differential scanning calorimetry (DSC) are as follows: scanning rate: 10°C / min; protective gas: nitrogen.

[0056] TGA, namely thermogravimetric analysis, the thermogravimetric analysis (TGA) graph of the present application was collected on TA's TGA55, and the method parameters of thermogravimetric analysis (TGA) are as follows: scanning rate: 10°C / min; protective gas: nitrogen.

[0057] Unless otherwise specified, the following examples are all operated at room temperature. The "room temperature" is not a specific temperature value, but refers to a temperature range of 10-30°C.

[0058] The "stirring" described in the following examples is accomplished by conventional methods in the art, such as magnetic stirring or mechanical stirring, with a stirring speed of 50-1800 rpm, wherein the magnetic stirring is preferably 300-900 rpm, and the mechanical stirring is preferably 100-300 rpm.

[0059] The "separation" described in the following examples is accomplished by conventional methods in the art, such as centrifugation or filtration, and the "centrifugation" operation is: placing the sample to be separated in a centrifuge tube and centrifuging it at a rate of 10,000 rpm until all the solids sink to the bottom of the centrifuge tube.

[0060] The "drying" described in the following examples can be carried out at room temperature or higher. The drying temperature is from room temperature to about 50°C, or to 40°C. The drying time can be 2 to 48 hours, or overnight. The drying is carried out in a fume hood, a forced air oven, or a vacuum oven.

[0061] The "crystals" described in the following examples refer to solids confirmed by X-ray powder diffraction patterns. It will be appreciated by those skilled in the art that the physicochemical properties discussed herein can be characterized, and the experimental errors therein depend on the conditions of the instrument, the preparation of the sample and the purity of the sample. In particular, it is well known to those skilled in the art that the X-ray powder diffraction pattern will usually change with different instrument conditions. It should be particularly noted that the relative intensity of the diffraction peaks in the X-ray powder diffraction pattern may also change with the change of experimental conditions, so the order of the diffraction peak intensity cannot be used as the only or decisive factor. In fact, the relative intensity of the diffraction peaks in the X-ray powder diffraction pattern is related to the preferred orientation of the crystal, and the diffraction peak intensity shown in the present invention is illustrative rather than for absolute comparison. In addition, the experimental error of the diffraction peak position is usually 5% or less, and the errors of these positions should also be taken into account, and an error of ±0.2 is usually allowed. In addition, due to the influence of experimental factors such as sample thickness, the overall offset of the diffraction peak angle will be caused, and a certain offset is usually allowed. Therefore, it can be understood by those skilled in the art that the X-ray powder diffraction pattern of the protected crystal form of the present invention is not necessarily completely consistent with the X-ray powder diffraction patterns in the embodiments referred to herein, and any crystal form having an X-ray powder diffraction pattern that is the same as or similar to the characteristic peaks in these patterns falls within the scope of the present invention.

[0062] A person skilled in the art can compare the X-ray powder diffraction patterns listed in the present invention with the X-ray powder diffraction patterns of an unknown crystal form to confirm whether the two sets of patterns reflect the same or different crystal forms.

[0063] The crystal form DCIII of the present invention is pure and substantially free of any other crystal forms. In the present invention, "substantially free" when used to refer to a new crystal form means that the crystal form contains less than 20% (by weight) of other crystal forms, particularly less than 10% (by weight) of other crystal forms, more particularly less than 5% (by weight) of other crystal forms, and even more particularly less than 1% (by weight) of other crystal forms.

[0064] The term "about" in the present invention, when used to refer to a measurable value, such as mass, time, temperature, etc., means that there is a certain floating range around the specific value, which can be ±10%, ±5%, ±1%, ±0.5% or ±0.1%.

[0065] The ferric maltol as a raw material includes, but is not limited to, solid form (crystalline or amorphous), oily form, liquid form and solution. Preferably, it is in solid form.

[0066] The preparation method of the ferric maltol crystal form DCIII of the present application is as follows: ferric maltol is placed in an organic solvent, and the obtained mixture is stirred, separated, and dried to obtain the crystalline form DCIII. Specifically, ferric maltol is added to a chlorinated hydrocarbon to form a suspension, the chlorinated hydrocarbon is a compound containing the element chlorine, and the chlorinated hydrocarbon here can be selected from any one of dichloromethane and chloroform or a mixture of the two, and then the suspension is placed at a low temperature (preferably 0 to 5 degrees) and stirred, and after centrifugation to separate the solid, the crystalline form DCIII is obtained after drying at a high temperature for a period of time.

[0067] The above-mentioned recrystallization process needs to be carried out at a specific temperature. The temperature used in this application is -20 to 30°C, preferably 0 to 5°C.

[0068] The above drying temperature needs to be carried out at a constant temperature. The temperature used in this application is 100-180°C, preferably 150°C.

[0069] The maltol iron crystal form DCIII obtained in the present application can be in the form of tablets or capsules when administered. For patients who have difficulty swallowing solid forms, liquid preparations can also be used when the medicament is orally taken. For the preparation of tablets or capsules, conventional adjuvants can be added and prepared in a conventional manner. For example, when preparing tablets, the maltol iron crystal form DCIII obtained in the present application is mixed evenly with the adjuvants, rolled into thin slices and crushed into particles, mixed evenly with the added adjuvants, and pressed into shape using a suitable mold. When preparing capsules, the maltol iron crystal form DCIII obtained in the present application is mixed evenly with the adjuvants, rolled into thin slices and crushed into particles, mixed evenly with the added adjuvants, and canned into capsules of suitable size.

[0070] The maltol iron crystal form DCIII prepared in the present application can be used in drugs for preventing or treating iron deficiency with or without anemia in subjects, and can be used to treat subjects with iron deficiency.

[0071] Symptoms and signs of iron deficiency, before the onset of iron deficiency anemia, include fatigue, hair loss, convulsions, irritability, dizziness, brittle nails or appetite disorders, impaired immune function, and slow growth in children. Conditions associated with iron deficiency anemia include chronic kidney disease, systemic lupus, rheumatoid arthritis, gastrointestinal diseases, etc.

[0072] Example 1

[0073] Weigh 5 grams of maltol iron, add 25 milliliters of chloroform, and then place the sample at 0°C and stir overnight; after centrifugation to separate the solid, place the sample at 150 degrees to dry for ~1 hour to obtain crystals, namely, crystal form DCIII. Its XRPD pattern is as follows Figure 1 The XRPD data are shown in Table 1, and the DSC diagram is shown in Figure 2 shown.

[0074] Table 1

[0075]

[0076]

[0077] from Figure 2 It can be seen that the ferric maltol crystal form DCIII prepared in Example 1 begins to show an endothermic peak at around 292°C.

[0078] Example 2

[0079] Weigh 300 mg of maltol iron into a 5 ml glass vial, add 1.5 ml of chloroform solution, stir overnight at 5°C, centrifuge to separate the solid, and heat to 150°C in an oven to obtain a sample, which is the crystal form DC III. Its XRPD pattern is as follows Figure 3 The XRPD data are shown in Table 2. Figure 3 It can be seen that the ferrous maltol prepared in Example 2 is the crystal form DCIII.

[0080] Table 2

[0081]

[0082] Example 3: Solubility of the Crystalline DCIII in Biological Media

[0083] When conducting drug solubility tests to predict the performance of the drug in vivo, it is important to simulate in vivo conditions as closely as possible. For oral drugs, SGF (simulated gastric fluid), FaSSIF (fasted state simulated intestinal fluid), and FeSSIF (fed state simulated intestinal fluid) can simulate in vivo conditions and predict the effects of eating. The solubility tested in such media is closer to the solubility in the human body environment.

[0084] In order to compare the solubility of Form II in the original crystal patent CN107001310 and the crystal DCIII of the present application in biological media, the experiment was conducted with reference to the USP method for determining the solubility of biological media. Experimental method: Weigh about 25 mg of the crystal DCIII prepared in Example 1, add 1 ml of SGF (simulated gastric fluid), FaSSIF (simulated intestinal fluid in fasting state), FeSSIF (simulated intestinal fluid in fed state) buffer solution, stir at a constant temperature of 37°C ± 1°C, take samples at 1h and 2h, and take the supernatant to determine its content by HPLC. Form II in the CN107001310B patent was also sampled as above. The experimental conditions and results are shown in Table 3.

[0085] Table 3

[0086]

[0087] The solubility experimental results in biological solvents show that compared with the crystal form Form II in the CN107001310B patent, the crystal form DCIII of the present invention has higher solubility in SGF (simulated gastric fluid), FaSSIF (fasting state simulated intestinal fluid), and FeSSIF (fed state simulated intestinal fluid).

[0088] Example 4: Solubility of the crystalline form DCIII of the present application in water

[0089] The solubility of the thermally stable crystalline form Form II in water is disclosed in paragraph

[0219] of the CN107001310B patent. The solubility of the crystalline form DCIII of the present invention in water was tested in the same manner. The results are shown in Table 4 below:

[0090] Table 4

[0091]

[0092]

[0093] The results of the solubility experiment in water show that compared with the crystal form Form II in the CN107001310 patent, the crystal form DCIII of the present invention has higher solubility in water.

[0094] Example 5 Stability of the Crystalline DCIII of the Present Application

[0095] About 5 mg of the crystal form DCIII prepared in Example 1 was weighed and placed at room temperature (25°C / 60%RH) and accelerated conditions (40°C / 75%RH, 60°C / 75%RH), and the crystal form was determined by XRPD and the chemical purity was determined by HPLC. The experimental conditions and results are shown in Table 5, and the XRPD overlay is shown in Table 5. Figure 4 shown.

[0096] Table 5

[0097] Placement conditions Placement time Crystal form Purity (peak area %) Starting —— Crystalline DCIII 99.96 25℃ / 60%RH 2 weeks Crystalline DCIII 99.96 40℃ / 75%RH 2 weeks Crystalline DCIII 99.96 60℃ / 75%RH 2 weeks Crystalline DCIII 99.95

[0098] The results show that the crystal form DCIII of the present invention can maintain physical and chemical stability for at least 2 weeks under three conditions: 25°C / 60% RH, 40°C / 75% RH, and 60°C / 75% RH.

[0099] Example 6 Mechanical stability of the crystal form DCIII of the present application

[0100] 10 mg of the crystalline DCIII prepared in Example 1 was placed in a mortar and manually ground for 15 minutes. XRPD tests were performed before and after grinding. Figure 5 shown.

[0101] according to Figure 5 It can be seen that the crystal form of the DCIII of the present invention remains unchanged after grinding, and no obvious decrease in crystallinity is observed, which indicates that the DCIII crystal form has good mechanical stability.

[0102] Example 7: Humidity stability of the crystal form DCIII of the present application

[0103] In order to understand the stability of the crystal form DCIII of the present application under different humidity conditions, and to further understand the risk of crystal transformation that may occur during the preparation of raw materials, formulation process, and storage of drugs, stability experiments of the crystal form DCIII under different humidity conditions were specially carried out.

[0104] Weigh ~10 mg of the sample of crystalline DCIII into a vial, open it and place it under different humidity conditions. After 2 weeks, the solid crystalline form was tested again. The results are shown in Table 6 below. The XRPD overlays before and after placement are shown in Figure 6 shown.

[0105] from Figure 6 It can be seen that after the crystal form DCIII of the present application is placed under different humidity conditions for 2 weeks, the crystal form remains unchanged and is still the crystal form DCIII. The crystal form DCIII of the present invention has excellent stability under both low humidity and high humidity.

[0106] During the preparation, storage and formulation of APIs, the environmental humidity will vary with factors such as season, location, and weather, so the stability of samples under different humidity conditions is an important parameter to be investigated. The crystal form DCIII of the present invention has good stability under both low and high humidity conditions, which will facilitate the sample production, storage and formulation processes, reduce the risk of crystal transformation, and improve product stability.

[0107] Table 6

[0108]

[0109] Example 8: Hygroscopicity of the Crystalline DCIII of the Present Application

[0110] The hygroscopicity was determined according to the guidelines for drug hygroscopicity experiments in General Chapter 9103 of the 2020 edition of the Chinese Pharmacopoeia. The test conditions were: 25±1°C, 80% relative humidity.

[0111] Definition of hygroscopic weight gain:

[0112] Very hygroscopic: weight gain due to moisture absorption is not less than 15.0%;

[0113] Hygroscopic: weight gain due to moisture absorption is less than 15.0% but not less than 2.0%;

[0114] Slightly hygroscopic: weight gain due to moisture absorption is less than 2.0% but not less than 0.2%;

[0115] No or almost no hygroscopicity: moisture gain is less than 0.2%.

[0116] About 20 mg of the crystalline DCIII prepared in Example 1 of the present application was weighed and placed under conditions of 25±1° C. and 80% relative humidity for 24 hours, and the mass of the sample before and after was recorded. The specific results are shown in Table 7 below.

[0117] Table 7

[0118]

[0119] As can be seen from Table 7, the crystalline DCIII of the present invention is slightly hygroscopic, which indicates that the crystalline DCIII is not prone to deliquescence during drug production and storage.

[0120] The preferred specific embodiments of the present invention are described in detail above. It should be understood that ordinary technicians in the field can make many modifications and changes based on the concept of the present invention without creative work. Therefore, all technical solutions that can be obtained by technicians in the technical field based on the concept of the present invention through logical analysis, reasoning or limited experiments on the basis of the prior art should be within the scope of protection determined by the claims.

Claims

1. Compound I of crystal form.

2. The crystalline form DCIII of compound I according to claim 1, characterized in that: Using Cu-Ka radiation, its X-ray powder diffraction pattern has characteristic peaks at one, two or three of the 2theta values ​​of 13.8°±0.2°, 9.4°±0.2° and 14.4°±0.2°.

3. The crystalline form DCIII of compound I according to claim 2, characterized in that: Using Cu-Ka radiation, its X-ray powder diffraction pattern has characteristic peaks at one, two or three of the 2theta values ​​of 6.8°±0.2°, 10.6°±0.2° and 15.1°±0.2°.

4. The crystalline form DCIII of compound I according to claim 2, characterized in that: Using Cu-Ka radiation, its X-ray powder diffraction pattern has characteristic peaks at one, two or three of the 2theta values ​​of 15.8°±0.2°, 22.9°±0.2° and 24.0°±0.2°.

5. A method for preparing the crystalline form DCIII of compound I according to claim 2, characterized in that: A certain amount of compound I is weighed and added into a glass bottle, a certain amount of organic solvent or a mixed solvent of organic solvents is added, and the mixture is fully shaken, recrystallized at a certain temperature, and the solid is separated by centrifugation and dried at a certain temperature to obtain the crystalline form DCIII.

6. The preparation method according to claim 5, characterized in that: The selected organic solvent is chloroform; the selected recrystallization temperature is preferably -20 to 30 degrees, more preferably 0 to 5 degrees; the selected drying temperature is preferably 100 to 180 degrees, more preferably 150 degrees.

7. The present invention also provides a pharmaceutical composition, which comprises an effective therapeutic amount of crystalline DCIII and a pharmaceutically acceptable carrier or excipient.

8. Furthermore, the present invention provides the use of crystalline DCIII in the preparation of a medicament for preventing or treating iron deficiency with or without anemia in a subject.

Citation Information

Patent Citations

  • crystalline form of maltol iron

    CN107001310B

Cited By

  • Crystal form dciii of ferric maltol, and preparation method therefor and use thereof

    WO2026067690A1